Research hotspots and trends of sarcopenia in orthopaedic surgery: a bibliometric analysis from 2003 to 2023 - Li, Ruijiang; Ge, Yufeng; Chen, Yixiao; Liu, Gang; Gao, Feng; Tu, Chao; Li, Ting; Wang, Ling; Yang, Minghui; Wu, Xinbao (Frontiers in Surgery, 2025)
PurposeThis study aimed to evaluate the current bibliometric characteristics, progress, and hotspots of cross-sectional research on orthopaedic surgery and sarcopenia over the past two decades.MethodsPublications related to sarcopenia and orthopaedic surgery, published between January 2003 and December 2023, were screened the Web of Science Core Collection. The bibliometric analysis and data visualization processes—including assessments of authors, countries, institutions, keywords, and references—were conducted with Microsoft Office Excel, VOSviewer, CiteSpace, and the Bibliometrix (R package).ResultsA total of 1,815 documents authored by 8,592 researchers from 2,376 organizations across 77 countries and published in 285 journals were identified. The United States led in both publication volume and total citations. The University of Melbourne had the highest number of publications, while Osteoporosis International emerged as the core journal in this field, with the highest number of publications, citations, and H-index. Cawthon PM was the most influential author, with 21 publications and 3,271 citations. Keywords were categorized into four clusters: Cluster 1 (epidemiology and pathophysiology of sarcopenia), Cluster 2 (clinical outcomes), Cluster 3 (management), and Cluster 4 (physical function). The most common keywords were mainly about “sarcopenia”, “body composition”, “muscle strength”, “hip fracture” and “mortality”.ConclusionsThe bibliometric results indicated a steady and rapid increase in the field of sarcopenia and orthopaedic surgery from 2003–2023. Previous research has predominantly focused on the epidemiology, pathophysiology, clinical outcomes, physical function, and management of sarcopenia. Future research in the intersection of sarcopenia and orthopaedic surgery is likely to delve into the molecular mechanisms of muscle-bone crosstalk, and multidisciplinary management of elderly sarcopenic patients in the orthopaedic field.